2012
DOI: 10.1115/1.4007634
|View full text |Cite
|
Sign up to set email alerts
|

Movement of the Distal Carpal Row During Narrowing and Widening of the Carpal Arch Width

Abstract: Change in carpal arch width (CAW) is associated with wrist movement, carpal tunnel release, or therapeutic tunnel manipulation. This study investigated the angular rotations of the distal carpal joints as the CAW was adjusted. The CAW was narrowed and widened by 2 and 4 mm in seven cadaveric specimens while the bone positions were tracked by a marker-based motion capture system. The joints mainly pronated during CAW narrowing and supinated during widening. Ranges of motion about the pronation axis for the hama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This led to palmar bowing of the transverse carpal ligament and increases in the carpal arch height (CAH) and the carpal arch area (CAA). Additionally, it was shown that inter-carpal joint mobility provides flexibility for CAW narrowing (Gabra et al, 2012, Li et al, 2009), leading to carpal arch formation which benefits the carpal tunnel environment by accommodating physiological variations of pressure in the tunnel. Also, a study examining the morphological changes of the carpal tunnel in response to the carpal tunnel pressure showed that an increase in the tunnel pressure is associated with a decrease in the CAW and an increase in the tunnel circularity, contributing to an increase in the carpal tunnel area (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This led to palmar bowing of the transverse carpal ligament and increases in the carpal arch height (CAH) and the carpal arch area (CAA). Additionally, it was shown that inter-carpal joint mobility provides flexibility for CAW narrowing (Gabra et al, 2012, Li et al, 2009), leading to carpal arch formation which benefits the carpal tunnel environment by accommodating physiological variations of pressure in the tunnel. Also, a study examining the morphological changes of the carpal tunnel in response to the carpal tunnel pressure showed that an increase in the tunnel pressure is associated with a decrease in the CAW and an increase in the tunnel circularity, contributing to an increase in the carpal tunnel area (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…elliptical, of the carpal tunnel. The anisotropic stiffness behavior can also be linked to the directionally dependent anatomical constraints of the wrist such as ligamentous connections and bone congruence (Gabra et al, 2012). The wrist is a complex joint composed of many obscurely shaped bones interconnected by numerous ligaments with multiple articulations.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to experimentation, each specimen was preconditioned by displacing the ridge of the trapezium by 2 mm in a set of the 14 directions; the order of the 14 directions was randomized within a set, and the preconditioning was repeated for 10 sets. A preconditioning magnitude of 2 mm was chosen because it is the largest displacement magnitude used for testing and the carpal arch remains relatively elastic within this amount of displacement (Gabra et al, 2012; Li et al, 2013; Xiu et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…The difference in compliance in the inward and outward directions is likely due to the direction-dependent stabilizing role of the TCL as well as the other intercarpal ligaments. [20][21][22] The role of the intercarpal ligaments in stabilizing the bony arch was also shown by Garcia-Elias et al, who applied compressive force to the carpal tunnel in the dorsal-palmar direction to quantify the rigidity of the tunnel with and without an intact TCL. 23 In contrast to the compliance in the radio-ulnar direction, 19 the carpal tunnel stiffness in the dorsal-palmar direction 23 was not affected by transecting the TCL because of the other intercarpal ligaments in the tunnel structure.…”
Section: Biomechanics Of the Carpal Tunnelmentioning
confidence: 99%